The Intensity Tajweed in Muraja’ah of Tahfidz Learning in Elementary Schools - Qonita, Farra Risti; Sutama, S; Adnan, Mazlini (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study examines the critical role of tajwīd in elementary‐school tahfīz learning, aiming first to describe how lengthening and shortening (mad) are applied during murājaʿah in accordance with tajwīd rules, and second to outline the instructional process for teaching the phonetic properties of letters (such as tafkhīm and tarqīq) within the same framework. Methodology: Employing a qualitative ethnographic design, the research was conducted at the Integrated Islamic Elementary School Muhammadiyah Al‑Kautsar in Gumpang, Kartasura. Participants included the school principal, the tahfīz coordinator, the tahfīz teacher, and fifth‑grade students. Data were gathered through in‑depth interviews, participatory classroom observations of murājaʿah sessions, and analysis of relevant documents. To ensure rigor, both source triangulation (multiple informants) and method triangulation (interviews, observations, documentation) were applied. Data analysis followed an inductive approach, allowing themes to emerge organically from the field evidence. Results: Findings indicate that precise application of mad significantly enhances the quality of students’ recitation and safeguards the intended meanings of Qur’anic verses by preventing pronunciation errors. Additionally, systematic instruction in letter properties— distinguishing between tafkhīm (heavy articulation) and tarqīq (light articulation)—was shown to improve students’ pronunciation accuracy, reinforcing their mastery of tajwīd principles during both individual and group practice. Applications/Originality/Value: By providing an ethnographically grounded account of tajwīd pedagogy at the elementary level, this study offers practical insights for curriculum developers and tahfīz instructors seeking to strengthen foundational recitation skills. Its detailed description of mad implementation and sifat‐huruf instruction can inform teacher training programs and serve as a model for other primary‐school tahfīz programs aiming to preserve both the linguistic and spiritual integrity of Qur’anic recitation.